How similar is the stellar structure of low-mass late-type galaxies to that of early-type dwarfs? - Janz, Joachim; Lisker, Thorsten (Arxiv, 2016)
We analyse structural decompositions of 500 late-type galaxies (Hubble $T$-type $\ge 6$) from the Spitzer Survey of Stellar Structure in Galaxies (S$^4$G), spanning a stellar mass range of about $10^7$ to a few times $10^{10}$ M$_\odot$. Their decomposition parameters are compared with those of the early-type dwarfs in the Virgo cluster from Janz et al. They have morphological similarities, including the fact that the fraction of simple one-component galaxies in both samples increases towards lower galaxy masses. We find that in the late-type two-component galaxies both the inner and outer structures are by a factor of two larger than those in the early-type dwarfs, for the same stellar mass of the component. While dividing the late-type galaxies to low and high density environmental bins, it is noticeable that both the inner and outer components of late types in the high local galaxy density bin are smaller, and lie closer in size to those of the early-type dwarfs. This suggests that, although structural differences between the late and early-type dwarfs are observed, environmental processes can plausibly transform their sizes sufficiently, thus linking them evolutionarily.